Flow of Products of Thermal Decomposition of Oil Shale Through Porous Skeleton; AIP Conference Proceedings; Vol. 1783 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2016 - Knyazeva A. G. Anna Georgievna (2016, 2016)
Title screen